Gefapixant, a P2X3 receptor antagonist, for the treatment of refractory or unexplained chronic cough: a randomised, double-blind, controlled, parallel-group, phase 2b trial. Issue 8 (August 2020) - Smith, Jaclyn A; Kitt, Michael M; Morice, Alyn H; Birring, Surinder S; McGarvey, Lorcan P; Sher, Mandel R; Li, Yu-Ping; Wu, Wen-Chi; Xu, Zhi Jin; Muccino, David R; Ford, Anthony P; ,; et al.
Summary: Background: Gefapixant is a P2X3 receptor antagonist that has shown promise for the treatment of refractory and unexplained chronic cough. The aim of this study was to evaluate the efficacy of gefapixant compared with placebo after 12 weeks of treatment for refractory chronic cough or unexplained chronic cough. Methods: We did a 12-week, phase 2b, randomised, double-blind, placebo-controlled study in patients with refractory chronic cough or unexplained chronic cough aged 18–80 years who were recruited from 44 primarily outpatient pulmonologist or allergist sites in the UK and the USA. Eligible patients had refractory or unexplained chronic cough lasting 1 year or longer, no radiographic chest abnormality, and 40 mm or more on a 100-mm cough severity visual analogue scale at enrolment. Patients were randomly assigned to receive placebo or one of three doses (7·5 mg, 20 mg, or 50 mg) of oral gefapixant twice daily, every day, for 84 days; visits to investigative sites were on days 1, 28, 42, 56, 70, 84, and 85. The randomisation schedule was computer generated using a permuted block algorithm by Advance Research Associates (Santa Clara, CA, USA). Patients and all personnel involved in the conduct and interpretation of the study were masked to treatment assignment. The primary endpoint was placebo-adjusted change from baseline in awake cough frequency after 12 weeks, assessed in the full analysis set, which is a subset of the intention-to-treat population. Adverse events were monitored and safety was evaluated in all patients receiving one or more doses of study drug. This trial is registered with ClinicalTrials.gov, NCT02612610 . Findings: Between Dec 21, 2015, and July 26, 2016, 253 patients were randomly assigned to placebo (n=63), gefapixant 7·5 mg (n=64), gefapixant 20 mg (n=63), or gefapixant 50 mg (n=63) twice daily. The mean age of patients was 60·2 (SD 9·9) years and 193 (76%) were women. At 12 weeks, patients' geometric mean awake cough frequency was 18·2 coughs per h (geometric SD 3·1) with placebo, and 14·5 coughs per h (3·7) with 7·5 mg, 12·0 coughs per h (4·2) with 20 mg, and 11·3 coughs per h (2·8) with 50 mg gefapixant. Estimated percentage change relative to placebo was −22·0% (−41·8 to 4·6; p=0·097) with 7·5 mg, −22·2% (−42·0 to 4·3; p=0·093) with 20 mg, and −37·0% (95% CI −53·3 to −14·9; p=0·0027) with 50 mg gefapixant. Dysgeusia was the most common adverse event, occurring in three (5%) patients given placebo, six (10%) given 7·5 mg gefapixant, 21 (33%) given 20 mg gefapixant, and 30 (48%) given 50 mg gefapixant. Interpretation: Targeting purinergic receptor P2X3 with gefapixant at a dose of 50 mg twice daily significantly reduced cough frequency in patients with refractory chronic cough or unexplained chronic cough after 12 weeks of treatment compared with placebo. Further development of gefapixant is warranted for the treatment of chronic cough. Funding: Afferent Pharmaceuticals (acquired by Merck & Co., Inc., Kenilworth, NJ, USA).